INTERSUBJECTIVE FAILURE AND QUEST FOR MUTUAL RECOGNITION: A PSYCHOANALYTIC STUDY OF THIS HOUSE OF CLAY AND WATER BY MANSAB AND AMERICANAH BY NGOZI (Contemporary Journal of Social Science Review, 2025)
This study aims to investigate how intersubjective failure and the quest for mutual recognition impact the psychological growth of the characters in the novels, This House of Clay and Water by Faiqa Mansab, and Americanah by Chimamanda Ngozi Adichie. Jessica Benjamin’s psychoanalytical theory of intersubjectivity and mutual recognition has been used as a theoretical framework to uncover the psychological depth of the characters’ experiences. Moreover, the researchers have also examined how the dominant ideologies integrated into the texts cause hinderance to the development of genuine intersubjective relations. Using a psychoanalytic framework, it has been analyzed how characters in said texts struggle for acknowledgment, belonging, and selfhood by transcending the complementary relations through shared third and moral third. In This House of Clay and Water, the protagonist’s emotional isolation shows patriarchal misrecognition, but her bond with a transgender gives an exceptional moment of mutual recognition. In Americanah, the protagonist’s blog becomes a powerful space where she engages with intersubjectivity. The findings suggest that the lack of intersubjectivity and mutual recognition leads to isolation, alienation, and existential pessimism.